Emerging role of management education for growing and developing Agri-business in Indian scenario: a Review / Virupaxayya Kulkarni - Kulkarni, Virupaxayya (Universiti Teknologi Mara, Selangor: Puncak Alam Campus, 2019)
In India, agriculture is considered as the backbone of its economy. It has been around since ancient times when other sectors were not even in existence yet. Today agriculture has achieved commercial importance and one of the powerful sectors contributing to nations' GDP. The population of our country is increasing day by day and the size of land remains same. So, with increasing productivity, another important concept is "MANAGEMENT". Agribusiness Management Education is a discipline that blends economic, agriculture, business (commerce) and management principles. In agriculture education, management field is gaining popularity day by day. Since the last few decades, agriculture has achieved satisfactory growth but due to some factors, the agricultural growth is relatively stagnated. So, upgradation is needed, right from pre harvesting until it reaches at the consumer level. Farmers are key performers in farming but are not able to get good returns to his produce due to many middlemen in the marketing channel. Due to a growing population, it creates a disparity between market demand and supply. So, proper management practices are required including reducing raw material wastage at farm and processing level and effective marketing strategies are also needed. Hence, an attempt is made in this paper to study the role of management education in agri-business sector and how it will help in developing managerial skills and to develop management workforce to cater for the Indian agricultural industry which serves as a good option for potential employment in corporate sector.